Two-step activity-based protein profiling of diacylglycerol lipase. Issue 29 (13th July 2018) - van Rooden, Eva J.; Kreekel, Roy; Hansen, Thomas; Janssen, Antonius P. A.; van Esbroeck, Annelot C. M.; den Dulk, Hans; van den Berg, Richard J. B. H. N.; Codée, Jeroen D. C.; van der Stelt, Mario
Abstract : Diacylglycerol lipases (DAGL) produce the endocannabinoid 2-arachidonoylglycerol, a key modulator of neurotransmitter release. Abstract : Diacylglycerol lipases (DAGL) produce the endocannabinoid 2-arachidonoylglycerol, a key modulator of neurotransmitter release. Chemical tools that visualize endogenous DAGL activity are desired. Here, we report the design, synthesis and application of a triazole urea probe for DAGL equipped with a norbornene as a biorthogonal handle. The activity and selectivity of the probe was assessed with activity-based protein profiling. This probe was potent against endogenous DAGLα (IC50 = 5 nM) and it was successfully applied as a two-step activity-based probe for labeling of DAGLα using an inverse electron-demand Diels–Alder ligation in living cells.